Modeling diffuse midline glioma through triple-electrode in utero electroporation of the developing mouse pons - Madisen S. Mason; Hosbaldo Morales Murillo; Madisyn G. Dudek; Samantha E. Maher; Santos J. Franco (PLoS ONE, 2026)
The leading cause of brain cancer–related death in children is diffuse midline glioma (DMG). A particularly aggressive DMG subtype is pontine DMG (formerly diffuse intrinsic pontine glioma, DIPG), which is caused by the histone mutation H3.3K27M. Because of its diffuse growth and location in a critical brainstem structure, therapeutic options are limited, and pontine DMG is considered universally fatal. The lack of appropriate animal models has hindered our understanding of the developmental origins and progression of pontine DMG, which in turn has limited the development of effective therapeutics. To address this barrier, several labs have developed mouse in utero electroporation approaches to express canonical DMG mutant oncogenes in the developing pons. In this manuscript and accompanying protocol, we describe a modified in utero electroporation strategy to generate DMG tumors in the developing mouse pons. Our protocol incorporates a single plasmid construct that expresses canonical DMG oncogenes, eliminating the need to co-electroporate multiple plasmids. We also employ a triple-electrode configuration to precisely target neural progenitors lining the fourth ventricle, which give rise to cells in the pons. As the embryos continue to develop in utero and postnatally, they form large, diffuse brainstem tumors with molecular characteristics of pediatric pontine DMG, allowing us to model the formation and progression of this deadly pediatric brain cancer.